Fisheries Recources Status of Rasbora (Rasbora sp) in Rawa Pening, Semarang, Central Java: Bioeconomic Analysis - Nopisari, Dian Ayunita NN. Dewi (Agriekonomika, 2016)
Rasbora (Rasbora sp) is natural resources which have potency to catch in Rawa Pening Swamp. Total production of rasbora was 11,930 kg in 2014. The research objectives to analyzed rasbora bioeconomic status with Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and Open Access (OA) indicators in Rawa Pening. Bioeconomic analysis for Rasbora used Gordon-Schaefer Model. Primary data obtained with census and the total respondents were 31 gillnet fishers. Primary data were gillnet efforts, price and cost of rasbora fishing. Secondary data used Rasbora (Rasbora sp) production for 10 years from 2003-2012. The result of Gordon-Schaefer model for Maximum Sustainable Yield produced of rasbora (CMSY) of 44,100 kg/year with fishing efforts (EMSY) 21,000 efforts/year. The Maximum Economic Yield status (CMEY) 35,916.08 kg/year with effort maximum (EMEY) of rasbora 11,953 efforts/year. Meanwhile, limitation of the rasbora production in Open Access Equilibrium (COAE) was 43,000 kg/year and effort maximum (EOAE) 23,766 efforts/year. Rasbora resources in Rawa Pening status is in underfishing condition.